PROGRAM PENDIDIKAN PROFESI ARSITEK (Sebuah Tanggapan akan diberlakukannya Pendidikan Profesi Arsitek, sebagai pendidikan tambahan bagi lulusan program Strata 1 Arsitektur untuk berprofesi sebagai ARSITEK) - DJOKO PRATIKTO (Jurnal Teknik Sipil dan Arsitektur, 2008)
To work professionally a graduate of the .scholar SI Architecture still could not be carried out or was not yet acknowledged by the world community of the practice of architecture, except for this graduate has been experienced for 3 years in architeceure, or beforehand had wrought/the apprentice in the Consultant's company Architecture or through professional education architecture that was held by the educational agency or the organisation of the profession. This reality could be seen in the condition to memilki the professional certificate of the architect's expertise that was issued by the organisation of the Association of the Indonesian Architect (IAI) and the Development Agency of the Construction Service that is the Architect's certificate request "Pratama "(the Architect the Beginner) had the minimal experience 3 years in the planning field/architecture planning. This condition was not possible to be valid for graduate just/the scholar of strata architecture 1 that was not yet experienced anything.To become the professional architect must be waiting 3 years and had the experience in the architecture field The association of the Indonesian Architect (IAI) the organisation of the architect's entitled profession gave to the acknowledgment formally (certification) co-operated with Directorate General Might Education Departemen of National Education planned the Professional educational Program the Architect as additional education for I (one) the year after strata education 1 to become the solution to this problem above. That became the necessary question the additional program of this architecture education. The study was supervised this was the response from being planned by a Program of Education of the Architect's Profession by IAI and DIKTI. Â